Severe anaemia in children living in a malaria endemic area of Kenya. - Newton, C; Warn, P; Winstanley, P; Peshu, N; Snow, R; Pasvol, G; Marsh, K (1997)
Severe anaemia is an important cause of morbidity and mortality in African children, but the causes, particularly falciparum malaria, are difficult to determine. We assessed the contribution of falciparum malaria to anaemia in Kenyan children by clinical examination and measurement of parasitaemia and haemoglobin (Hb) concentration in 559 children in the community and in 2412 children admitted to Kilifi district hospital during a 2-year period. We also attempted to characterize severe malarial anaemia by examining the causes and pathophysiology of anaemia in 101 children admitted with Hb concentration < or = 50 g/l during a 1-year period. Plasmodium falciparum infection was associated with reduced Hb concentration in children in the community and in those admitted to hospital irrespective of diagnosis. Falciparum malaria was the primary cause in 46 cases (46%) of severe anaemia admitted to hospital. There was no difference in the frequency of haemolysis or dyserythropoiesis in the children with malarial anaemia and those with anaemia from other causes, such as iron deficiency or sickle cell disease. The mortality rate in the children with severe malarial anaemia was 8.6% compared with 3.6% in children with severe anaemia due to other causes. Falciparum malaria does not present with a characteristic clinical or haematological picture, but is a major cause of the morbidity and mortality in children with severe anaemia who live on the Kenyan coast, a malaria endemic area.